Auditoría de gestión a los procesos administrativos y financieros de la cooperativa de ahorro y crédito OCCIDENTAL ubicada en el cantón Pujilí, período 2018. - Amores Pruna, Andrea Estefanía (2020)
Management Audit is an analysis and diagnosis that is performed in an entity with the purpose of advising for decision-making.This project was carried out in the Savings and "Occidental" Credit Union Ltda. Located in Pujilí canton, province of Cotopaxi, in this institution an audit of this type has not been carried out previously, which has caused a lack of knowledge of implementing appropriate policies and procedures to successfully achieve the proposed goals for the organization. The purpose of the Management Audit was aimed to determine the compliance of the administrative and financial processes for which efficiency, effectiveness and quality indicators were applied. For the development of this work study, it has a deductive approach because it was possible to establish critical areas, it is qualitative and quantitative since it evaluates the key processes and values that are established throughout the period, it is also scientific, descriptive since it was developed in the credit union´s facilities in order to obtain true data, with techniques and methods such as: the observation form and the application of internal control questionnaires.The results obtained showed the existence of weaknesses in the fulfilment of procedures mainly from manuals that require accomplishment, lack of POA (Annual Operating Plan) for monitoring, realization of objectives and budget, function manuals, performance evaluation. The audit has contributed to the formulation of recommendations and conclusions to improve the financial administrative processes of the credit union